CD4 T cells correlate with better prognosis in medulloblastoma - Zhang, Jin; Ren, Siqi; Li, Shuting; Wang, Yuan; Wan, Lulu; Gao, Wenchao; Sun, Huaying; Gong, Xiaojun; Li, Miao; Sun, Yanling; Sun, Liming; Li, Zhigang; et al. (Frontiers in Oncology, 2025)
ObjectiveT cells and tumor-associated macrophages (TAMs) are critical immune components within the brain tumor microenvironment (TME), yet their precise roles in medulloblastoma remains unclear. In this study, we examined the infiltration characteristics of T cells in medulloblastoma tissues and analyzed the correlation between T cells and the clinical outcomes of medulloblastoma patients. Additionally, we further investigated the relationship between T cells and TAMs.MethodsWe enrolled a total of 72 patients diagnosed with medulloblastoma and subsequently detected the T cell makers and programmed death 1/programmed death-ligand 1 (PD-1/PD-L1) in paraffin-embedded sections using multiple immunofluorescence staining method. The correlation between T cell infiltration, clinical characteristics and prognosis were analyzed. Finally, we used Spearman correlation analysis to evaluate the correlation between T cells and TAMs.ResultsThe median age at diagnosis of 72 patients (54 boys, 18 girls) was 7.5 years (range: 0.8–18 years). These patients included 43 cases of classic medulloblastoma (CMB), 24 cases of desmoplastic/nodular medulloblastoma (DNMB), 2 cases of medulloblastoma with extensive nodularity (MBEN) and 3 cases of large-cell/anaplastic medulloblastoma (LCA). The molecular subgroups consisted of 3 wingless (WNT), 29 sonic hedgehog (SHH) and 40 non-WNT/non-SHH cases. Twenty-five cases presented with metastasis at diagnosis, while 47 cases were without metastasis. Thirteen cases exhibited with high-risk genetic abnormalities. The total T cells (P = 0.031) and CD4 T cells (P = 0.045) were significantly elevated in the SHH subgroup compared to those in the non-WNT/non-SHH subgroup. Patients with increased CD4 T cells had better 5-year PFS (P = 0.000) and OS (P = 0.001), while patients without metastasis showed better 5-year PFS (P = 0.031) and OS (P = 0.015). Multivariate analysis showed that CD4 T cells were an independent prognostic factor affecting both the 5-year PFS (P = 0.004, HR = 0.230, 95% CI = 0.085-0.662) and OS (P = 0.017, HR = 0.180, 95% CI = 0.044-0.739). Additionally, it was observed that CD4 T cells exhibited a positive correlation with Mtotal (total macrophages) (P < 0.05, r = 0.249) and Mmix (M1/M2 mixed phenotype macrophages) (P < 0.01, r = 0.325), and CD3+CD8+PD-1+ cells showed a positive correlation with Mmix (P < 0.05, r = 0.258).ConclusionThe increase in CD4 T cells predicts a better prognosis in medulloblastoma patients, particularly within the SHH and non-WNT/non-SHH subgroups, and they may serve as a potential therapeutic target for medulloblastoma. Additionally, there may be a potential interaction between CD4 T cells and TAMs that warrants further investigation.